2021
DOI: 10.1002/jbm4.10513
|View full text |Cite
|
Sign up to set email alerts
|

Regular Strength and Sprint Training Counteracts Bone Aging: A 10‐Year Follow‐Up in Male Masters Athletes

Abstract: Cross‐sectional and interventional studies suggest that high‐intensity strength and impact‐type training provide a powerful osteogenic stimulus even in old age. However, longitudinal evidence on the ability of high‐intensity training to attenuate age‐related bone deterioration is currently lacking. This follow‐up study assessed the role of continued strength and sprint training on bone aging in 40‐ to 85‐year‐old male sprinters (n = 69) with a long‐term training background. Peripheral quantitative computed tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Densiometric values derived from computer tomography at 10 years of training revealed that well-trained sprinters had better bone properties than less-trained ones (p < 0.05). The main effect was seen in lower and mid-tibial trabeculae [30].…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Densiometric values derived from computer tomography at 10 years of training revealed that well-trained sprinters had better bone properties than less-trained ones (p < 0.05). The main effect was seen in lower and mid-tibial trabeculae [30].…”
Section: Resultsmentioning
confidence: 87%
“…Stimuli such as compression and fl uid shear are crucial for osteoblastic activity and the maintenance of a healthy bone mass and density [29]. Sprint-trained athletes exhibit observable structural adaptations as a thickened cortical loaded area, which is one of the reasons for effective directionspecifi c bending strength [30].…”
Section: ключевые словаmentioning
confidence: 99%
“…These side-specific loading adaptations were generally maintained five years later, despite decreases in average training volume [53]. Similarly, a ten-year longitudinal follow-up of male sprinters found that those who maintained a high training volume were protected against age-related decreases in tibia trabecular bone density observed in those who decreased their training volume [54].…”
Section: Retrospective Studiesmentioning
confidence: 89%
“…(56,57) In addition, some studies in middle-aged and older men indicate that the maintenance of a high osteogenic index or loading intensity, rather than total time spent in physical activities, is associated with greater skeletal benefits at the loaded sites. (58)(59)(60) Therefore, it is possible that among former athletes, even a modest amount of participation in vigorous-intensity exercise (75 minutes/week), may have been effective in counteracting age-related decline in femoral neck strength, thus reducing the probability of a hip fracture in the case of a fall. Another explanation might be that continued vigorous exercise helps to protect against fractures through other mechanisms such as preserved rapid muscle force capacity (20) and dynamic postural balance (61) that could reduce the frequency of falls and/or facilitate effective protective responses during a fall.…”
Section: Discussionmentioning
confidence: 99%